Exploration of Case-Based Collaborative Participatory Learning in International Human Resource Management Course - Andriyastuti Suratman (Jurnal Lingua Idea, 2022)
This study aims to explore learning with case-based learning (CBL) approach to increase student participation individually and collaboratively. This study used quantitative methods to know the students response with the case-based learning process that was implemented in International Human Resource Management (HRMI) classes. As 125 respondents filled out an online questionnaire by Google Form. The following are the results of the research: 1) lecturers deliver lecture materials communicatively and have an essentials role as an opening in the learning process to stimulate enthusiasm, participation, and understanding that leads to how far the level of student satisfaction in the learning process; 2) student participation in the discussion of the material was only 59.2% of the total respondents, this happened due to the reduction in the duration of lectures during the pandemic. To coping this phenomenon, lecturers prepared video material for each chapter in each meeting to be accessed independently. 3) less than half of the respondents were active in discussing cases (48.8%). It is relevant to the findings of students feeling afraid/anxious to show up/talk in discussing cases. The results indicate that lectures performance have significant effect on students' enthusiasm, participation, understanding, and satisfaction more and less with a percentage range from 12.9% to 43.1%. Also, the level of students' understanding that emerged from this case-based learning method was as much as 30.9%, which was understood from the beginning to involved in the value component other than the mid-term and final exams. Study for the future is the need to give more attention to class ratios, learning media (face-to-face or virtual), the readiness of the technology used by teachers and class participants, and how relevant the cases with the lecture material delivered.